Intercropping of corn with some selected legumes for improved forage production: a review - Belel, Mustapha Dauda; Abd Halim, Mohd Ridzwan; Yusop, Mohd Rafii; Mohd Saud, Halimi (Canadian Center of Science and Education, 2014)
Low forage quality and low corn yield experienced due to continuous monoculture resulting from persistent soil depletion in the developing world have generated the need for a sustainable practice to improve quality and yield of aforementioned. This review examines the salient issues that relates to the effect of intercropping some selected legume in different cropping patterns with corn in order to improve the yield and forage quality of corn, and that of quality feed/forage production. Two legumes species namely: Bambara groundnut and Peanut were the key crops focused with the main corn crop in this review work.